Особливості взаємодії злоякісних клітин і пухлин з хіміотерапевтичними нанокомпозитними лікарськими засобами - Туранська, С.П.; Крупська, Т.В.; Туров, В.В.; Горбик, П.П. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2023)
The purpose of the review is to find, generalize and analyze scientific data related to the specifics of the interaction of chemotherapeutic official drugs and nanocomposites based on them with malignant cells and tumors, primarily characterized by the emergence of drug resistance, the determination of promising directions and ways to overcome it, and the creation of new effective nanocomposite remedies for use in antitumor chemotherapy. The given data indicate the relevance of the topic. Targeted studies of the resistance of malignant cells and neoplasms to chemotherapeutic drugs have been carried out since the 1990s. The majority of works were performed according to the methodology, that involves the traditional use of chemotherapeutic drugs. In these works, the principle of the multifactorial nature of resistance was determined, the processes and mechanisms of its implementation were studied, related to the reduction of the accumulation of the chemotherapeutic drug in cells, the increase in the activity of detoxification systems, the strengthening of DNA repair processes, the reduction of apoptosis, and autophagy. A number of promising substances and influencing factors contributing to overcoming of resistance have been identified. However, the discovered ways to overcome the resistance of malignant cells and neoplasms to the corresponding drugs are at the stages of laboratory, preclinical, or, in the best case, clinical research. At the same time, it is not excluded that the use of the latest highly effective chemotherapeutic drugs will lead to the emergence of new mechanisms of resistance. Thus, at this time the results of research on the traditional use of chemotherapeutic drugs constitute a significant fundamental and practically important development regarding the determination of mechanisms of drug resistance, however, the problem of its medicinal overcoming remains far from being solved, and the used approaches give the impression of dead ends. With the development of nanotechnology, new scientific directions have been initiated and a significant amount of researches has been carried out, devoted to the creation and search for promising applications in oncology of nanocomposites based on bioinert, biocompatible and bioactive nanoparticle materials and modern chemotherapeutic drugs. It should be emphasized that all these works contain data indicating the advantages of introducing nanocomposite drugs into clinical practice, compared to the use of chemotherapeutic drugs in traditional forms. Against this background, purposeful researches are distinguished carried out by scientists of O.O. Chuiko Institute of Surface Chemistry of National Academy of Sciences of Ukraine and R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of National Academy of Sciences of Ukraine in the field of creation of modern polyfunctional nanocomposite chemotherapeutic agents for use in antitumor therapy, capable of overcoming drug resistance of malignant cells and neoplasms. So, at O.O. Chuiko Institute of Surface Chemistry of National Academy of Sciences of Ukraine for the first time magnetic fluids were synthesized containing antitumor drugs cisplatin, doxorubicin, gemcitabine, corresponding antibodies, their physicochemical properties were studied, and parameters for standardization were determined. At R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of National Academy of Sciences of Ukraine the antitumor properties of magnetic fluids were studied. On the basis of magnetic fluid with cisplatin, the first native magnetosensitive oncological drug "Feroplat" has been proposed, which has no analogues in the world. Feroplat is a standardized tool for increasing the effectiveness of chemotherapy and overcoming drug resistance of malignant neoplasms, intended for the delivery of cytostatics directly to the tumor tissue. This ensures its maximum entry into the cells and helps to increase the therapeutic effect. In order to introduce "Feroplat" into production and clinical practice, its preclinical tests were successfully performed. The analysis of the given data indicates the priority of works in the field of creation of new nanocomposite chemotherapeutic drugs for use in antitumor therapy, capable of overcoming drug resistance of malignant cells and neoplasms. The facts of overcoming the drug resistance of malignant neoplasms to cisplatin with the new native oncological drug "Feroplat", as well as high indicators of cytotoxic / cytostatic activity of nanobiocomposites based on saline solution, magnetite and cisplatin, doxorubicin, gemcitabine, etc., may indicate the fundamental need to change approaches to the use of modern antitumor chemotherapeutic agents – by replacing their traditional molecular forms with appropriate nanocomposite forms.